Meningkatkan Motivasi Belajar Siswa Melalui Penerapan Sistem Reward Pada Mata Pelajaran IPA Kelas IV SDN 5 Kabila - Stepaniya I. Mohamad; Yulanti S. Mooduto; Aida Nursyaida (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to improve students’ learning motivation through the implementation of a reward system in science learning for fourth-grade students at SDN 5 Kabila. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 23 students. Data were collected through observation, interviews, documentation, and tests. Data analysis used percentage techniques to measure students’ learning motivation individually and classically, with the success indicator defined as at least 80% of students achieving a high level of learning motivation. The results showed that the implementation of the reward system significantly improved students’ learning motivation. In the initial condition, only 17.4% of students had high learning motivation. After the implementation in Cycle I, motivation increased to 65%, but it had not yet reached the success indicator. In Cycle II, students’ learning motivation increased to 91%, indicating that most students had achieved a high level of motivation. In conclusion, the implementation of a well-planned and consistent reward system is effective in improving students’ learning motivation in science learning.